2011
DOI: 10.5657/fas.2011.0323
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Suitable Species of Chlorella, Nannochloris, and Nannochloropsis in High- and Low-Temperature Seasons for Mass Culture of the Rotifer Brachionus plicatilis

Abstract: To find seasonally optimal microalgae for mass culture of the rotifer Brachionus plicatilis, the growth rates of 12 microalgal species (two marine Chlorella spp., five marine Nannochloris spp., two marine Nannochloropsis spp., one estuarine Nannochloropsis sp., and two estuarine Chlorella spp.) were compared at 25°C at 15 psu and 30 psu. Among these, six species showing high growth rates were chosen and examined again at high (30°C and 32°C) and low (10°C) temperatures. Their amino and fatty acids and the diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The outer shell is rough if compared to the latest SEM of C.sorokiana [51].The feature is almost the same as found in SEM of C.vulgaris [52]. In terms of size, the specimen was found to be in between the size of marine C.vulgaris (2.1µm) and estuarine C.vulgaris (2.3µm) from Korean waters [53]. The cell has an average cell biovolume of 5.26±0.87 µm 3 .…”
Section: Results and Discussion Experiments 1: Production Of Chlorellasupporting
confidence: 56%
“…The outer shell is rough if compared to the latest SEM of C.sorokiana [51].The feature is almost the same as found in SEM of C.vulgaris [52]. In terms of size, the specimen was found to be in between the size of marine C.vulgaris (2.1µm) and estuarine C.vulgaris (2.3µm) from Korean waters [53]. The cell has an average cell biovolume of 5.26±0.87 µm 3 .…”
Section: Results and Discussion Experiments 1: Production Of Chlorellasupporting
confidence: 56%
“…Similarly, Eikassas, [50] have reported 0.15% of DHA content in Pichochloruim sp., cultivated under nitrogen starvation. Besides, Bea and Hur [51] have found the DHA content of 0.29% and 0.02% in Nannochlorosis sp., and N. oculata respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results on the growth rate and composition of 12 marine species from different taxonomic groups as food for Brachionus plicatilis, subsequently used as food for marine fish (mainly Pagrus major), indicated Nannochloropsis sp. (KMMCC-33) as 'the best microalgal species for the mass culture of the rotifer' [66]. An alternative method of culturing N. oculata by using green water from red tilapia (Oreochromis sp.)…”
Section: Vitamins and Use Of Eustigmatophyceae As Food For Humans Andmentioning
confidence: 99%
“…Therefore, considering the increased interest in these fatty acids for human consumption, in order to meet the demands of the expanding market, it is essential to search for novel algal sources. Studies have shown a high content of EPA in marine Nannochloropsis (up to 44% of the total fatty acid content -TFA) and its potential application for human diet [66,[82][83][84][85][86]. Research has vastly concentrated on testing the optimal growth conditions, of environmental conditions and on the effects of nutrients and nutrient starvation for obtaining the maximum EPA yield in different types of reactors [59,84,85,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: Lipids (Fatty Acids and Sterols) Of Eustigmatophyceaementioning
confidence: 99%
See 1 more Smart Citation